Identifying temperature breaks in pome fruit and table grape export cold chains from South Africa to the United Kingdom and the Netherlands : a Western Cape case - Fedeli, Savia (Stellenbosch : Stellenbosch University, 2019)
Thesis (MCom)--Stellenbosch University, 2019.